Effect of whey protein hydrolysate on performance and recovery of top-class orienteering runners - Hansen, M.; Bangsbo, J.; Jensen, J.; Bibby, B. M.; Madsen, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
This trial aimed to examine the effect of whey protein hydrolysate intake before and after exercise sessions on endurance performance and recovery in elite orienteers during a training camp. Eighteen elite orienteers participated in a randomized controlled intervention trial during a 1-week training camp (13 exercise sessions). Half of the runners (PRO-CHO) ingested a protein drink before (0.3 g kg-1) and a protein-carbohydrate drink after (0.3 g protein kg-1 and 1 g carbohydrate kg-1) each exercise session. The others ingested energy and timematched carbohydrate drinks (CHO). A 4-km run-test with 20 control points was performed before and on the last day of the intervention. Blood and saliva were obtained in the mornings, before and after run-tests, and after the last training session. During the intervention, questionnaires were fulfilled regarding psychological sense of performance capacity and motivation. PRO-CHO and not CHO improved performance in the 4-km run-test (interaction p < .05). An increase in serum creatine kinase was observed during the week, which was greater in CHO than PRO-CHO (interactionp < .01). Lactate dehydrogenase (p < .001) and cortisol (p = .057) increased during the week, but the change did not differ between groups. Reduction in sense of performance capacity during the intervention was greater in CHO (p < .05) than PRO-CHO. In conclusion, ingestion of whey protein hydrolysate before and after each exercise session improves performance and reduces markers of muscle damage during a strenuous 1-week training camp. The results indicate that protein supplementation in conjunction with each exercise session facilitates the recovery from strenuous training in elite orienteers.